Pengaruh Pelatihan Kerja, Lingkungan Kerja, dan Motivasi Kerja Terhadap Kinerja Karyawan di PT Aerofood Indonesia Unit Surabaya - Rilafilista Muju; Rina Indra Sabella (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
Employee performance is a crucial factor in the aviation food service industry, which demands punctuality, service quality, food safety, and high work coordination. These conditions require companies to manage human resources optimally through appropriate job training, a supportive work environment, and strong work motivation. This study aims to analyze the influence of job training, work environment, and work motivation on employee performance at PT Aerofood Indonesia Unit Surabaya. The study used a quantitative approach with explanatory research. Primary data were obtained through questionnaires distributed to 80 employees who were used as research respondents. Data were analyzed using multiple linear regression with the help of SPSS after meeting validity, reliability, and classical assumption tests. The results of the study indicate that job training, work environment, and work motivation have a positive and significant effect on employee performance, both partially and simultaneously. Among the three variables, work motivation provides the most dominant contribution to improving employee performance. This finding indicates that performance improvement does not only depend on technical competencies acquired through training, but is also influenced by the quality of the work environment and employees' psychological motivation in carrying out tasks. The results of this study are expected to be a consideration for companies in formulating sustainable human resource management policies.